2014
DOI: 10.1002/cpe.3240
|View full text |Cite
|
Sign up to set email alerts
|

Workload resampling for performance evaluation of parallel job schedulers

Abstract: SUMMARYEvaluating the performance of a computer system is based on using representative workloads. Common practice is to either use real workload traces to drive simulations or use statistical workload models that are based on such traces. Such models allow various workload attributes to be manipulated, thus providing desirable flexibility, but may lose details of the workload's internal structure. To overcome this, we suggest to combine the benefits of real traces and flexible modeling. Focusing on the proble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 61 publications
1
13
0
Order By: Relevance
“…Similar results have been obtained for the workloads on file systems [303], parallel machines [669,749], and more. Although self-similarity is basically a statistical property, it is hard to reproduce by a simple sampling from a distribution.…”
Section: Self-similaritysupporting
confidence: 83%
See 4 more Smart Citations
“…Similar results have been obtained for the workloads on file systems [303], parallel machines [669,749], and more. Although self-similarity is basically a statistical property, it is hard to reproduce by a simple sampling from a distribution.…”
Section: Self-similaritysupporting
confidence: 83%
“…For example, user resampling is a methodology to create multiple versions of the same basic workload by partitioning it into the subtraces representing different users, and then recombining them randomly to create new workloads. Interestingly, in the context of parallel job workloads at least, it has been shown that such manipulations do not affect the self-similarity of the workload [749]. This lends support to models such as the merged on-off processes described later.…”
Section: Validationmentioning
confidence: 60%
See 3 more Smart Citations